(untitled) (Itinera, 2015)
This paper aims at questioning what an improvisation in politics may mean. It analyzes specifically the reasons why some German activists as Rudi Dutschke and Bernd Rabehl saw the beginning of the Anti-autoritarian Movement in the manifestation against Tschombe of the 18th December 1964; and how they wanted to adopt Mao’s, Fanon’s and Che Guevara’s teachings in their struggle. Its goal is to understand this manifestation as a political improvisation insofar it created the style of Anti-Autoritarian movement of the sixties in West-Berlin.